The Role of Side Payments in the Formation of Asymmetric Alliances: Forging the US–Pakistan Alliance. (August 2019) - Kabir, Muhammad
Abstract: The article builds on James Morrow's theoretical formulation on asymmetric alliances, which contends that alliances are formed as a result of a security–autonomy trade-off between great powers and minor powers. It expands Morrow's theory by showing that in the absence of a common threat or shared interests, the trade-off tends to leave a deficit in a weaker state's net benefits from the alliance. I argue that side payments fill in the deficit in gains for weaker states. The article highlights the importance of domestic political constraints in shaping leaders' alliance policies. I use the US–Pakistan alliance as a case study to probe the argument. The analysis presented here shows that the alliance, formed in 1954, was a result of a strategic trade-off between the United States and Pakistan. The case provides support to the argument that side payments played a crucial role in cementing the alliance.